Neuron-Specific Enolase Predicts Poor Outcome After Cardiac Arrest and Targeted Temperature Management: A Multicenter Study on 1, 053 Patients. Issue 7 (July 2017) - Streitberger, Kaspar Josche; Leithner, Christoph; Wattenberg, Michael; Tonner, Peter. H.; Hasslacher, Julia; Joannidis, Michael; Pellis, Tommaso; Di Luca, Elena; Födisch, Markus; Krannich, Alexander; Ploner, Christoph J.; Storm, Christian
Abstract : Objective: Outcome prediction after cardiac arrest is important to decide on continuation or withdrawal of intensive care. Neuron-specific enolase is an easily available, observer-independent prognostic biomarker. Recent studies have yielded conflicting results on its prognostic value after targeted temperature management. Design, Setting, and Patients: We analyzed neuron-specific enolase serum concentrations 3 days after nontraumatic in-hospital cardiac arrest and out-of-hospital cardiac arrest and outcome of patients from five hospitals in Germany, Austria, and Italy. Patients were treated at 33°C for 24 hours. Cerebral Performance Category was evaluated upon ICU discharge. We performed case reviews of good outcome patients with neuron-specific enolase greater than 90 μg/L and poor outcome patients with neuron-specific enolase less than or equal to 17 μg/L (upper limit of normal). Measurements and Main Results: A neuron-specific enolase serum concentration greater than 90 μg/L predicted Cerebral Performance Category 4–5 with a positive predictive value of 99%, false positive rate of 0.5%, and a sensitivity of 48%. All three patients with neuron-specific enolase greater than 90 μg/L and Cerebral Performance Category 1–2 had confounders for neuron-specific enolase elevation. An neuron-specific enolase serum concentration less than or equal to 17 μg/L excluded Cerebral Performance Category 4–5 with a negative predictive value of 92%. The majority of 14 patients with neuron-specific enolase less than or equal to 17 μg/L who died had a cause of death other than hypoxic-ischemic encephalopathy. Specificity and sensitivity for prediction of poor outcome were independent of age, sex, and initial rhythm but higher for out-of-hospital cardiac arrest than for in-hospital cardiac arrest patients. Conclusion: High neuron-specific enolase serum concentrations reliably predicted poor outcome at ICU discharge. Prediction accuracy differed and was better for out-of-hospital cardiac arrest than for in-hospital cardiac arrest patients. Our "in-the-field" data indicate 90 μg/L as a threshold associated with almost no false positives at acceptable sensitivity. Confounders of neuron-specific enolase elevation should be actively considered: neuron-specific enolase–producing tumors, acute brain diseases, and hemolysis. We strongly recommend routine hemolysis quantification. Neuron-specific enolase serum concentrations less than or equal to 17 μg/L argue against hypoxic-ischemic encephalopathy incompatible with reawakening. Abstract : Supplemental Digital Content is available in the text.